Saṅgītasādhaka Śaśīkānta : prathama mrtyu-bārshikīra śraddhārghya - Goswāmī, Śaśīkānta, 1902-1976; Hājarikā, Atulacandra, 1906-; Dāsa, Yugala (Sabitā Sabhā, 1977)
Collection of articles on the life and works of the Assamese musician Sasikanta Goswami, 1902-1975; published on the occasion of Goswami's first death anniversary.